ggstThe role of tendon microcirculation in Achilles and patellar tendinopathy - Knobloch Karsten (Journal of Orthopaedic Surgery and Research, 2008)
Abstract Tendinopathy is of distinct interest as it describes a painful tendon disease with local tenderness, swelling and pain associated with sonographic features such as hypoechogenic texture and diameter enlargement. Recent research elucidated microcirculatory changes in tendinopathy using laser Doppler flowmetry and spectrophotometry such as at the Achilles tendon, the patellar tendon as well as at the elbow and the wrist level. Tendon capillary blood flow is increased at the point of pain. Tendon oxygen saturation as well as tendon postcapillary venous filling pressures, determined non-invasively using combined Laser Doppler flowmetry and spectrophotometry, can quantify, in real-time, how tendon microcirculation changes over with pathology or in response to a given therapy. Tendon oxygen saturation can be increased by repetitive, intermittent short-term ice applications in Achilles tendons; this corresponds to 'ischemic preconditioning', a method used to train tissue to sustain ischemic damage. On the other hand, decreasing tendon oxygenation may reflect local acidosis and deteriorating tendon metabolism. Painful eccentric training, a common therapy for Achilles, patellar, supraspinatus and wrist tendinopathy decreases abnormal capillary tendon flow without compromising local tendon oxygenation. Combining an Achilles pneumatic wrap with eccentric training changes tendon microcirculation in a different way than does eccentric training alone; both approaches reduce pain in Achilles tendinopathy. The microcirculatory effects of measures such as extracorporeal shock wave therapy as well as topical nitroglycerine application are to be studied in tendinopathy as well as the critical question of dosage and maintenance. Interestingly it seems that injection therapy using color Doppler for targeting the area of neovascularisation yields to good clinical results with polidocanol sclerosing therapy, but also with a combination of epinephrine and lidocaine.